How Do Governments Respond after Catastrophes? Natural-Disaster Shocks and the Fiscal Stance - Melecky, Martin; Raddatz, Claudio (2012)
Natural disasters could constitute a major shock to public finances and debt sustainability because of their impact on output and the need for reconstruction and relief expenses. This paper uses a panel vector autoregressive model to systematically estimate the impact of geological, climatic, and other types of natural disasters on government expenditures and revenues using annual data for high and middle-income countries over 1975-2008. The authors find that, on average budget, deficits increase only after climatic disasters, but for lower-middle-income countries, the increase in deficits is widespread across all events. Disasters do not lead to larger deficit increases or larger output declines in countries with higher initial government debt. Countries with higher financial development suffer smaller real consequences from disasters, but deficits expand further in these countries. Disasters in countries with high insurance penetration also have smaller real consequences but do not result in deficit expansions. From an ex-post perspective, the availability of insurance offers the best mitigation approach against real and fiscal consequences of disasters.